The locus amoenus in the boom era. On Tornando a Roma by Giovanni Giudici (Configurazioni. Research on contemporary poetry, 2024)
This essay analyzes the locus amoenus in Giovanni Giudici’s 1960 poem Tornando a Roma, published in il menabò. It explores how Giudici, during the economic boom era, subverts the traditional bucolic topos. The author demonstrates how even the rural past of Montesacro already contained the seeds of capitalist alienation, reflecting Giudici’s view on long-term capitalism. The essay examines the stylistic and metrical choices that push the lyrical poetry toward prose, while maintaining its poetic essence, and the contrast between the lyric self’s “courage” and “pride” and the “shame” and “idleness” of the surrounding environment.
Keywords: Giovanni Giudici; La vita in versi; Italian Poetry of the 1960s; Industry and Literature; Poetry and Politics